Wireless communication techniques, the right path to smart grid distribution systems: A review - Shebani, Hikma; Julai, Norhuzaimin; Ahmed, Musse Mohamud; Khan, Sheroz; Hameed, Shihab A.; Habaebi, Mohamed Hadi (IEEE, 2017)
The quality and reliability of electric power supply are the key_index_factors in the development of a society. However, most of issues of worry are in the distribution system (DS), which, in the newest designs of Supervisory Control and Data Acquisition (SCADA) system is being monitored by a central computer (CC). The CC in a DS is supplied by electronic devices, named Feeder_Remote Terminal_Units (FRTU), with operation data like current and voltage. The FRTUs found throughout the DS have the capabilities to start triggering actions to separate the portion of DS suffering an abnormal condition. However, the present grid suffers from its one way data communication installations. To address the challenges of the existing power grids, the use of the innovative communication technologies that have emerged over the recent past years along with wireless sensor network (WSN) play a fundamental role—leading eventually to the creation of smart grid Systems. This paper reviews the development of wireless communication technologies envisioned as full-duplex information exchange medium in the on-going discussion of Smart Grid Systems.